2016
DOI: 10.31235/osf.io/qgykj
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prepare versus Repair? Combining parental leave and family allowances for social investment against single-parent poverty

Abstract: Social investment is an emerging paradigm for European welfare states, often described as an abandonment of tax-benefit systems with generous income ‘transfers’ in favour of ‘in-kind’ policies and services.The position of single-parent families directly relates to one of the major critiques of the social investment strategy. Despite efforts to improve employment and make work pay to prevent poverty, European welfare states have witnessed disappointing trends in poverty (Vandenbroucke and Vleminckx, 2011). Cant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…This suggests that other factors play a role as well, as well as that paid leave and childcare can be complementary. More detailed analyses on longitudinal data, presented elsewhere, reached similar conclusions (Maldonado and Nieuwenhuis, 2015;Nieuwenhuis and Maldonado, 2015). This research also highlighted the fact that all families with children benefit from longer periods of paid leave, and that by facilitating employment paid leave reduces the poverty gap between single-parent and twoparent families.…”
Section: Notessupporting
confidence: 70%
“…This suggests that other factors play a role as well, as well as that paid leave and childcare can be complementary. More detailed analyses on longitudinal data, presented elsewhere, reached similar conclusions (Maldonado and Nieuwenhuis, 2015;Nieuwenhuis and Maldonado, 2015). This research also highlighted the fact that all families with children benefit from longer periods of paid leave, and that by facilitating employment paid leave reduces the poverty gap between single-parent and twoparent families.…”
Section: Notessupporting
confidence: 70%
“…According to Esping-Andersen (2002), lone mothers will usually need additional income support in order to escape poverty. The findings of Nieuwenhuis and Maldonado (2016) proved the positive effect of social protection benefits on poverty reduction of single parents. They found that parental leave facilitated employment among single parent families, in turn reducing their poverty.…”
Section: Single Parenthood As a New Social Riskmentioning
confidence: 84%
“…They found that parental leave facilitated employment among single parent families, in turn reducing their poverty. The transfers of family allowances were associated with a substantial reduction in poverty, particularly among single-parent families (Nieuwenhuis and Maldonado (2016).…”
Section: Single Parenthood As a New Social Riskmentioning
confidence: 99%
See 2 more Smart Citations